The Effect Of Sharia Supervisory Board, Board Of Commissioners And Board Of Directors On Islamic Social Reporting Disclosure At Sharia Commercial Banks In Indonesia - Anisa Binti Roikatul Janah; Siti Sundari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine the effect of sharia supervisory board, board of commissioners, and board of directors on Islamic Social Reporting disclosures. The kind of quantitative research using secondary data exists annual report. The research sample of 12 sharia commercial banks in Indonesia was determined by purposive sampling technique with an observation period from 2018 to 2022. The analytical of research using multiple linear regression with the help of SPSS software. The result of research shows that board of commissioners and board of directors does have significant effects on Islamic Social Reporting disclosures. However, the sharia supervisory board does not have insignificant effect on Islamic Social Reporting disclosures.